Treatment of Human Immunodeficiency Virus with Zidovudine and Tenofovir Regimen in India: A Comparative Effectiveness Study. - Sowmyanarayanan, Thuppal. (2017)
Abstract: Human Immunodeficiency Virus (HIV) is one of the leading causes of death among infectious diseases. The adult HIV prevalence in India is around 0.27%. Combination anti-retroviral therapy (ART) with tenofovir as a component is considered to be the most efficient drug regimen along with emtricitabine and efavirenz. However in resource limited settings, this combination is not preferred since it is considered very expensive. Inspite of higher rates of drug related toxicities zidovudine containing regimen with lamivudine and nevirapine is considered the first-line treatment of choice in resource limited settings, since they are less expensive. Comparative effectiveness studies from resource sufficient settings show that tenofovir containing regimen is the better treatment for HIV. But country specific studies are required to compare these two regimens and identify the best treatment for that setting. Hence the objective of this PhD dissertation is to compare the economic, clinical and quality of life outcomes in patients living with HIV on treatment with zidovudine (along with lamivudine and nevirapine) and tenofovir (emtricitabine and efavirenz) regimens from an infectious disease clinic, at a private tertiary care hospital in southern India. To achieve this objective we conducted four different projects: The first project documented the toxicities and the cost of treatment for six months in patients living with HIV, initiated on the current first-line zidovudine containing regimen. The study showed that approximately 30% of the patients experienced drug related toxicity. Overall costs spent on treatment for a period of six months excluding antiretroviral drugs (antiretroviral drugs are provided free of costs to patients by the government) was Indian Rupees (INR) 7,157, which was one-third the average income earned by the patients during the study period. Exploratory analysis comparing treatment costs, including both direct and indirect costs showed that, patients with drug related toxicities had to spend significantly more than patients without drug related toxicities, imposing an additional significant economic burden to the patients. In the second project we compared the data collected from patients initiated on both the regimens prior to implementation of the government sponsored free antiretroviral therapy program. Patients who could afford to pay opted for the expensive tenofovir containing regimen, while those who could not afford opted for a less expensive zidovudine containing regimen. Since our study was observational and ability to pay may have been associated with both selection of treatment regimen and other characteristics potentially influencing health, we used propensity score (PS) analysis to mitigate the potential confounding. Compared to patients receiving zidovudine regimen, patients receiving tenofovir regimen had fewer adverse drug reactions (47% vs. 11%, p-value: <0.01), requiring fewer regimen changes (36% vs. 3%, p-value <0.01). With PS, zidovudine regimen had 8 times more adverse drug reactions (p-value: <0.01). Opportunistic infections were similar between regimens without PS, while zidovudine regimen had 1.2 times (p-value: 0.63) more opportunistic infections with PS. Patients on tenofovir regimen gained more body mass index. Increase in CD4 levels and treatment adherence (>95%) was similar across regimens. Patients on a tenofovir regimen had better clinical outcomes with improved general health than patients on zidovudine regimen. The third project was a pragmatic randomized clinical trial comparing treatment naïve HIV positive patients started on zidovudine and tenofovir containing regimens based on costs, clinical and quality of life outcomes. Compared to patients on the zidovudine regimen patients on the tenofovir regimen had significantly fewer adverse drug reactions (89% vs 45%, p-value: <0.01) and required fewer regimen changes (35% vs 7%, p-value: <0.01). The proportion of patients on zidovudine regimen experiencing opportunistic infections exceeded the corresponding proportion for patients on the tenofovir regimen (46% vs 31%, p-value: 0.22). Patients on the tenofovir regimen tend to have better quality of life and improved CD4 values than patients on the zidovudine regimen. Overall treatment costs did not differ between the two regimens, however the cost of treatment in patients with adverse drug reactions or opportunistic infections or both was greater in patients receiving zidovudine regimen compared to those receiving tenofovir regimen. The study findings suggest that compared to zidovudine regimen, the tenofovir regimen has fewer adverse drug reactions and opportunistic infections with greater improvement in CD4 levels and quality of life. Fourth project was a cost effectiveness analysis between zidovudine vs. tenofovir regimens. Model parameters including median costs, quality adjusted life years from SF6D and EQ5D questionnaires, and transitional probabilities were obtained from the pragmatic randomized study (project 3). A decision tree analysis was performed to estimate the cost effectiveness for a period of one year. A Markov decision model was performed for calculating the long term incremental costs and quality adjusted life years. From payer perspective the tenofovir-containing regimen cost 8,091 Indian Rupees and conferred a health benefit of 0.02 QALYs compared to the zidovudine-containing regimen, yielding a cost-effectiveness ratio of 404,550 INR (6,525 USD) per QALY. The Markov model projected an incremental cost of 1,768,298 INR (USD 28,521) and an incremental health gain of 0.08 QALYs. From the patient perspective, the tenofovir-containing regimen reduced costs and improved health (decision tree analysis: 4,596 INR saved and 0.01 QALYs gained; Markov model: 44,413 INR saved and 0.08 QALYs gained). Based on the WHO-CHOICE criteria for cost effectiveness analysis, tenofovir-containing regimen was not cost effective with payer perspective, however was cost effective with patient perspective. In conclusion, this PhD dissertation comparing zidovudine and tenofovir containing regimens for HIV in India suggest that: Fewer proportions of patients on the tenofovir regimen had adverse drug reactions and opportunistic infections compared to zidovudine regimen. Cost of treatment due to adverse drug reactions and opportunistic infections and the necessity for regimen change due to adverse drug reactions were higher in patients receiving zidovudine regimen than those patients receiving tenofovir regimen. From patient perspective tenofovir-containing regimen saved costs and improved health in patient living with HIV. Hence steps should be taken to reduce the procurement costs for the tenofovir-containing regimen and to implement the tenofovir-containing regimen as the first-line treatment regimen for patients living with HIV in India.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Christine Wanke.; Committee: Joshua Cohen, Farzad Noubary, Mkaya Mwamburi, and Jayaprakash Muliyil.; Keywords: Public health, and Epidemiology.